Did growth and reforms increase citizens' support for the transition? - Roberto Golinelli; Riccardo Rovelli (Institute for the Study of Labor (IZA), 2011)
How did post-communist transformations affect people's perceptions of their economic and political systems? We model a pseudo-panel with 89 country-year clusters, based on 13 countries observed between 1991 and 2004, to identify the macro and institutional drivers of the public opinion. Our main findings are: (i) When the economy is growing, on average people appreciate more extensive reforms; they dislike unbalanced reforms. (ii) Worsening of income distribution and higher inflation interact with an increasing share of the private sector in aggravating nostalgia for the past regime. (iii) Cross-country differences in the attitudes towards the present and future (both in the economic and political dimensions) are largely explained by differences in the institutional indicators for the rule of law and corruption. (iv) Cross-country differences in the extent of nostalgia towards the past are mainly related to differences in the deterioration of standards of living.
urn:nbn:de:101:1-201107133499
Keywords: O11; O57; P2; P36; P52; 330; political economy; post-communist transition; economic reforms; economic performance; support for reforms; public opinion